Is it time to rethink U.S. entry and exit processes? - Neu, C. R. (Carl Richard), 1949-; Rand Infrastructure, Safety, and Environment (Organization). Homeland Security; Rand Corporation (Santa Monica, CA : RAND, 2009)
Managing the entry and exit of individual travelers at U.S. borders is an important aspect of border and homeland security, particularly given the longstanding difficulties the Department of Homeland Security (DHS) and the U.S. border protection apparatus has had in meeting legislatively mandated standards for identifying travelers and documenting their arrivals and departures. This paper outlines a number of questions regarding current entry and exit policies and procedures the answers to which may lead to helpful modifications. It also looks at questions surrounding the issue of whether pursuing current objectives for entry and exit processing--especially objectives established by Congress--represents the best use of DHS budgetary and managerial resources.
"RAND Homeland Security."
"RAND Infrastructure, Safety, and Environment."
"This paper is one of a series of short papers resulting from a research effort initiated by the RAND Corporation during the transition in presidential administration in 2008-2009"--Preface.
"This research was conducted under the auspices of the Homeland Security Program within RAND Infrastructure, Safety, and Environment (ISE)"--Preface. IV.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Terrorism -- United States -- Prevention; Visas -- Government policy -- United States; Visitors, Foreign -- Government policy -- United States; United States -- Emigration and immigration -- Government policy